Peramalan Harga Cabai Menggunakan Metode High Order Fuzzy Times Series Multifactors - Ridho Agung Gumelar; Budi Darma Setiawan; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The daily needs of Indonesian people can not be separated from agricultural commodities such as chili, onion, garlic, tomatoes and others. Some of these agricultural commodities have sharp price fluctuations, such as chili. When the supply of chilli in the market decreases, the price can be soar higher than the normal price. Conversely, when the supply of chili is excessive, the price will be fall well below the normal price. This is influenced by various factors such as the harvest season, the amount of production, the amount of public consumption, the area of the harvest area and others. Therefore we need a method to estimate the price off chili so that it can be used to support decision-making related to price issues. Forecasting is one solution to be able to estimate the price movement of chili commodities. The method used to forecast the price of chili is High Order Fuzzy Times Series Multifactors. In this method the formation of subinterva is done by using Fuzzy C-means. For calculate forecasting error results in this research using Mean Square Error (MSE). Based on the results of the test, the value of training data and orders used in forecasting does not guarantee a low error rate. The results of forecasting the price of chili using the method of High Order Fuzzy Times Series Multifactors get the best MSE results of 20,374.19.